Financial Functions and New Trends - Mishra, Vijay Prakash (Journal of Commerce and Trade, 2014)
Retail financial services have just entered a new stage of development in India. This is evident, for example, in the fact that an increasing number of banks are allocating substantial management resources to various areas of retail financial services. Behind this movement is a business strategy among banks to strengthen their profitability, now that the nonperforming-loan (NPL) problem has been nearly overcome. Enhancement of retail financial services, however, is not a trend seen only in India, but it has been a common feature in financial industries worldwide since the 1990s. Considering that the Indian financial system is regaining its stability, we at the Bank of India has taken a number of steps with the intention of contributing to developing and spreading advanced financial technologies through our functions of on-site examinations and off-site monitoring to encourage financial institutions’ efforts to provide more advanced financial services.